A low-overpotential nature-inspired molecular chromium water oxidation catalyst. (1st March 2018) - Shamsipur, Mojtaba; Taherpour, Avat (Arman); Sharghi, Hashem; Lippolis, Vito; Pashabadi, Afshin
Abstract: The function of tyrosine Yz in photosystem II (PSII) has been considered as a model for establishing a new homogeneous water oxidation catalyst (WOC). In this work, we designed and synthesized a diphenoxy-based salen-type Schiff base ligand (L ) in order to overcome the problems that so far have prevented the use of chromium complexes as water oxidation catalysts (WOCs). Cyclic voltammetry measurements performed in the alkaline solution of [Cr(L-2H )Cl] (1 ) displayed a large irreversible oxidation waves, corresponding to the catalytic water oxidation. The main species in the catalytically active solutions is found to be [Cr(L -2H)ClOH] - ∙ The proposed catalytic system generates a current density (J) of 1.0 mA cm −2 at the relatively low overpotential (ƞ) of 0.426 V with a high turnover frequency (TOF) of 49.7 s −1 . A comprehensive mechanistic study was carried out based on the results of experiments, calculations and according to previous works. The computational calculations supported the importance of the uncoordinated OH groups present in the ligand moiety of the complex for the oxidation of Cr 3+ to Cr 4+ . Graphical abstract: Image 1